(untitled) - Koo, Jay (Thành phố Hồ Chí Minh, 2011)
Nội dung sách gồm các phần: Read a text aloud, describe a picture, respond to questions, respond to questions using information provided, propose a solution, express an opinion.
Keywords: English language,Tiếng Anh; Examinations,Kỳ thi